El anillo argénteo del Cerro de la Mesa (Toledo) y los anillos con caballito de la Hispania prerromana - Cano Martín, Juan José; Villar Liébana, Francisco; Almagro Gorbea, Martín; Ortega Blanco, José (Complutum, 1999)
Sin resumen